A institucionalização da indumentária gaúcha: imagens que (re)vestem o tradicionalista gaúcho (1947 - 1989) - Betta, Edinéia Pereira da Silva (2018)
This research set reflections about the Gaucho Traditionalist Movement and analyses the selected imagery repertoire on the composition of the institutionalized Gaucha clothing. Clothing became the main element of the set of references selected by the movement from 1947, from it people embrace the constituted identity, create personas and declare themselves as Gauchos. Due to the intense use of historical references on the movement practices, the imaginary is reinforced and results in the connection of the present with the past, creating meanings, evoking it as the different and emphasizing "me" and "the other". Therefore, the aim of this research was to verify the textual and imagery sources used in the book "Indumentária Gaucha" of the writer Antonio Augusto Fagundes, identifying and analyzing the historical references and the fashion aspects that rebound on the composition proposed by the author, and approved by the Gaucho Traditionalist Movement from the second half of the twentieth century